Tema-Tema pada Puisi Anā wa Al-Nisā’ Karya Nizar Qabbani (Kajian Semantik) - Kusumastuti, Ratna; Idris, Mardjoko (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
This article aims to describe and analyze the themes and meanings contained in the poem Anā wa al-Nisā’ by Nizar Qabbani. The research method used is descriptive which describes and analyzes the themes of Anā wa al-Nisā’s poetry by Nizar Qabbani. The data collection technique used is the listening technique by taking notes starting from reading books, research and other articles related to the research topic. The results of this study are that the themes contained in Anā wa al-Nisā’ by Nizar Qabbani are very diverse, such as the themes of love, sadness, boredom, and also matters relating to women. Then there are several pronunciations that have denotative meanings in the first and second stanzas. While the pronunciation which is interpreted as connotation is found in the third stanza.